Limites e possibilidades da participação no Programa “Um milhão de cisternas” - Santos, Alisson Campos (2012)
This paper discusses the nature of participation in social and Mobilization Training Program for Living in the Semiarid - One Million Cisterns-P1MC. To this end, we discuss as the issue of water has remained in the development agenda of the semiarid and how the P1MC has been presented as an alternative to the democratization of water in the region. We investigated the deployment process P1MC in three municipalities in the semiarid paraibano: Patos, São José de Espinharas e Malta. The three municipalities are located within range of the Patos Diocesan Social Action (ASCP) that acts locally as a Manages Unit Microregional (UGM) of the P1MC (PB-03). Were interviewed Twenty families with the objective to apprehend in what way the beneficiaries participate in the program at the local level and how families perceive the participatory process. It was found that participation was reduced to a formal character, procedural, the extent that the participatory process did not occur as a result of a work-sharing ideas and goals, but as an obligation to be fulfilled for acquiring the cistern. Featuring thus a participation subordinated, with protocolar character. It was also noted that the cisterns have not been sufficient to meet the needs of part of the families interviewed, while the distribution of water by tanker car remains a common practice in the daily life of the communities studied. However, the cistern has decreased the dependence of families and promoted a relative autonomy of water.